1970
DOI: 10.2136/sssaj1970.03615995003400020007x
|View full text |Cite
|
Sign up to set email alerts
|

Water Repellency and Infiltration Resistance of Organic‐Film‐Coated Soils

Abstract: Water repellency and infiltration resistance of porous soils coated with a variety of thin, organic films were examined. Water repellency was determined by measuring the effective contact angle of water resting on the soil surface and infiltration resistance was determined by measuring the breakthrough pressure, i.e., the threshold pressure required to force water into the soil pore structure of these water‐repellent soils. The effective contact angle of water on these treated soils was found to be a function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…As pointed out before, this implies that the contact angle M exceeds 90". Further extrapolation of this equation shows that the classification criterion of 90" (Rietveld, 1978 andFink, 1970) is reached at a WDPT of 0.07 s, a'i=O supposedly occurring at a WDPT of 0~000000016 s. These non-measurable quantities are probably inaccurate but it is possible to conclude that the soil material in question has an a which exceeds 90" if its WDPT exceeds 1 s. Wa=non-repellent IIIb =slightly repellent IIIc = strongly repellent…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As pointed out before, this implies that the contact angle M exceeds 90". Further extrapolation of this equation shows that the classification criterion of 90" (Rietveld, 1978 andFink, 1970) is reached at a WDPT of 0.07 s, a'i=O supposedly occurring at a WDPT of 0~000000016 s. These non-measurable quantities are probably inaccurate but it is possible to conclude that the soil material in question has an a which exceeds 90" if its WDPT exceeds 1 s. Wa=non-repellent IIIb =slightly repellent IIIc = strongly repellent…”
Section: Resultsmentioning
confidence: 99%
“…This means that all samples must be labelled extremely water repellent according to the classification by Rietveld (1978). When the classification suggested by Fink (1970) is used, all samples are termed water repellent. The values of the WDPT varied between 2 and 2051 s, so according to the index proposed by Adams et al (1969) the samples had to be placed in different categories: two samples were non-repellent, three samples were slightly repellent, and ten samples were strongly repellent.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As examined by Dell'Avanzi et al (2010) and Subedi et al (2012), a possible technique to enhance the abilities of a capillary barrier and control seepage is to make the coarse-grained materials water repellent by mixing or coating them with hydrophobic agents (HAs). Various HAs have been tested to alter the hydrophobicity of grain surfaces: silicone resins, amine acetates, fluorochemicals (Fink 1970), polyoxyalkylated diethylenetriamine (Alexandrova et al 2011), dichlorodimethylsilane (DCMS) (Liu et al 2012), polytetrafluorethylene (Dell' Avanzi et al 2010), stearic acid (Leelamanie et al 2008;Subedi et al 2012;González-Peñaloza et al 2013), and oleic acid (OA; Subedi et al 2012). They reported that the hydrophobized grains were fully effective to repel the water, based on the results of tests of water repellency (WR) such as water drop penetration time (King 1981), molarity of an ethanol droplet test (Roy and McGill 2002) and sessile drop method (SDM; Bachmann et al 2000a, b).…”
mentioning
confidence: 99%